Approach Selection and Surgical Planning in Posterior Cranial Fossa Meningiomas: How I Do It - Beer-Furlan, André; Vellutini, Eduardo A.; Gomes, Marcos Q. T.; Cardoso, Alberto C.; Prevedello, Luciano M.; Todeschini, Alexandre B.; Prevedello, Daniel M. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Posterior cranial fossa meningiomas represent approximately 9% of all the intracranial meningiomas. Despite the recent reports of radiation therapy in the management of these tumors, surgical resection continues to be the first line of treatment method aiming the permanent meningioma eradication. The evolution of imaging studies improved the preoperative evaluation of meningiomas providing greater anatomical detail of small structures not previously visualized. Nonetheless, the preoperative radiological evaluation should go beyond the differential diagnosis of a posterior fossa tumor. Anatomo-radiological assessment of meningiomas is discussed in detail. Based on our clinical experience, literature review, and case illustration, we highlight important preoperative anatomo-radiological aspects of posterior fossa meningiomas and their implications in the surgical management of these tumors.
Keywords: meningioma; posterior fossa; clival meningioma; petroclival meningioma; foramen magnum meningioma; jugular foramen meningioma; cerebellopontine angle meningioma; surgical approaches